Entry trajectory optimization for hypersonic vehicle based on time-scales separation guidance with waterweeds algorithm - Xudong Liu; Lin Cheng; Qingzhen Zhang; Lingtong Jiang (2016 IEEE Chinese Guidance, Navigation and Control Conference (CGNCC), 2016)
This paper focuses on the hypersonic vehicle in consideration of oscillation and aerodynamic heating problems during reentry process, for trajectory optimization, penalty function method and ε level comparison are introduced for transforming the unconstrained waterweeds algorithm into constrained algorithm to solve multi-objective optimization problems, in which a novel and more precise criterion based on time-scales separation guidance for oscillation optimization is put forward indicating waterweeds algorithm to get a better optimal result. The algorithm transformed is successfully applied to trajectory design.